Production of yoghurt from kefir beverage: Analysis of fermentation kinetics, volatile organic compounds, texture, and microbial characteristics - Bicer, Yusuf; Turkal, Gamze; Sonmez, Gonca; Telli, A. Ezgi; Bayir, Tuba; Culha, M. Hudai; Sert, Durmus (Elsevier Sci Ltd, 2024)
The study aims to produce yoghurt from kefir beverage and evaluate its fermentation kinetics, volatile organic compounds, texture, and microbial characteristics. Kefir, a fermented milk product, is known for its health benefits due to probiotic microorganisms. To improve its sensory properties, kefir was combined with yoghurt starter cultures (Lactobacillus delbrueckii and Streptococcus thermophilus), sodium caseinate, and lactose, and incubated for 12 and 24 h. Comprehensive analyses were conducted on the obtained yoghurts, encompassing fermentation parameters (pH and acidity), volatile organic compounds, and textural properties. The levels and viability of specific microorganisms within the samples were examined through propidium monoazide quantitative PCR (PMA-qPCR). The results showed that samples with Na-caseinate had higher firmness, consistency, and cohesiveness. Viscosity increased with the addition of Na-caseinate and lactose after 24 h. PMA-qPCR analysis revealed higher microorganism levels in samples with Na-caseinate and lactose. Solid-phase microextraction (SPME) and gas chromatography-mass spectrometry (GC-MS) analysis showed that diacetyl was the most common compound, and acetaldehyde and diacetyl levels decreased in yoghurts compared to kefir beverages. PMA-qPCR revealed that Streptococcus thermophilus had higher viability in samples with both Nacaseinate and lactose, while Lactobacillus delbrueckii had the highest viability in samples that contained only Na-caseinate incubated for 12 h. The study suggests that kefir-based yoghurt can be developed into a product with better sensory qualities and increased consumer appeal due to improved texture and aroma.
Keywords: Kefir yoghurt; Texture; PMA-qPCR; Volatile organic compounds